Anode Materials: Nanosheets‐Assembled CuSe Crystal Pillar as a Stable and High‐Power Anode for Sodium‐Ion and Potassium‐Ion Batteries (Adv. Energy Mater. 20/2019). Issue 20 (23rd May 2019) - Lin, Hezhe; Li, Malin; Yang, Xu; Yu, Dongxu; Zeng, Yi; Wang, Chunzhong; Chen, Gang; Du, Fei
Abstract : In article number1900323, Yi Zeng, Fei Du and co‐workers report the synthesis of a novel cubic phase CuSe crystal pillar which is self‐assembled by nanosheets, together with the dual functionality for high‐rate Na + and K + storage. A combination of in‐situ X‐ray diffraction and ex‐situ transmission electron microscopy tests, reveal the structural transition and phase evolution of CuSe that show a reversible conversion reaction for both cells.